Ubi Social, Ibi Ius Fondamenti costituzionali dei social network e profili giuridici della responsabilità dei provider - Allegri, Maria Romana (Studi di dritto pubblico - Open Access, 2018)
Through a constitutional framework of social networks and the deepening of the liability regime provided for digital intermediaries, in this book we try to understand if and how the existing legal rules, or those desirable in perspective de jure condendo, can offer valid solutions to overcome to the main problems that the enormous spread of these forms of communication poses.